Editorial - Lasker, Shamima Parvin (Bangladesh Journal of Bioethics, 2019)
Good care is the reflection of care ethical. To improve the ethical quality of care, moral behavior is needed in addition to law and regulation. Personal involvement and motivation of care providers are considered an important element of good care. Thus, health care provider must change their perspective. Their education on medical ethics needs to be more practical oriented rather than theory. In addition, ethical reflection is contextual and experiential learning process. Bioethics training must be needed to foster inter alia and moral power of imagination of care providers.